LOOK, THATS HOW I DO IT! TRY IT! : TEAMWORK SUPPORT WITH ONLINE TOOLS - Kállai, Gabriella (Tudásmenedzsment, 2024)
In Hungary, children and pupils with special educational needs are those who, on the basis of a diagnostic assessment by a committee of educational experts, are entitled to additional support for their development. Today, they are often placed in inclusive or integrative kindergartens and schools, where they learn with other children and are assisted in their development by a special needs teacher. Several studies have looked at the role of special needs teachers in inclusive education. Other approaches emphasise collaboration between professionals, and some forms of collaboration are seen as teamwork. Although these collaborations are necessary to achieve the best possible developmental outcomes, they are difficult to achieve for a number of reasons. This paper presents an action research project in which teamwork, i.e. case discussion, solution finding and knowledge transfer, took the form of online collaboration. The methodological framework was participatory action research. Although this form of collaboration was created out of necessity in the institution, the positive feedback and results from the participants show the need for activities and collective learning adapted to the knowledge level and needs of teachers, which help them to deal with everyday tasks and problems with more confidence and self-efficacy.